AIDS Activism and the Pharmaceutical Industry - Rehan Haider; Asghar Mehdi; Geetha Kumari; Zameer Ahmed; Sambreen Zameer (Contemporary Journal of Applied Sciences, 2024)
The intersection of AIDS activism and the pharmaceutical industry has been pivotal in remodeling public health responses and treatment accessibility for HIV/AIDS. In the Eighties and Nineteen Nineties, AIDS activists and considerable organizations like ACT UP played an essential role in the pharmaceutical industry's regulations and practices. these activists demanded quicker drug approval methods, low-cost medicinal drug pricing, and increased transparency in clinical trials. Their advocacy brought about extensive policy adjustments, which included the elevated approval process by using the U.S. Meals and Drug Administration (FDA) and the implementation of the 340B Drug Pricing application, which made medicines less expensive for underserved populations.The activism now not only compelled pharmaceutical industry to lower expenses but additionally stimulated the enterprise's research and improvement priorities, resulting in an extra-targeted attempt at HIV/AIDS remedies. Furthermore, the collaboration among activists, scientists, and healthcare providers fostered an environment conducive to large scientific breakthroughs, inclusive of the improvement of antiretroviral remedies (art), which has converted HIV/AIDS from a deadly disease to a doable, persistent situation.This dynamic interaction between activism and industry highlights the significance of civic engagement in shaping healthcare coverage and advancing scientific research